MiT/TFE Family of Transcription Factors: An Evolutionary Perspective - La Spina, Martina; Contreras, Pablo S.; Rissone, Alberto; Meena, Naresh K.; Jeong, Eutteum; Martina, José A. (Frontiers in Cell and Developmental Biology, 2021)
Response and adaptation to stress are critical for the survival of all living organisms. The regulation of the transcriptional machinery is an important aspect of these complex processes. The microphthalmia (MiT/TFE) family of transcription factors, apart from their involvement in melanocyte biology, are emerging as key players in a wide range of cellular functions in response to a plethora of internal and external stresses. The MiT/TFE proteins are structurally related and conserved through evolution. Their tissue expression and activities are highly regulated by alternative splicing, promoter usage, and posttranslational modifications. Here, we summarize the functions of MiT/TFE proteins as master transcriptional regulators across evolution and discuss the contribution of animal models to our understanding of the various roles of these transcription factors. We also highlight the importance of deciphering transcriptional regulatory mechanisms in the quest for potential therapeutic targets for human diseases, such as lysosomal storage disorders, neurodegeneration and cancer.